The Effect of Emotional Value, Social Value, Functional Value, and Perceived Price on Purchase Intention with Customer Attitude as Intervening Variable (A Case Study towards Nike Sport Shoes in Pontianak) - B12111008, Yuvika (Jurnal Manajemen Update, 2015)
The importance of value creation within a product or service has always been a great concern among the companies around the world. For some reasons, it affects the buyers’ perception on how they see a product before they buy. Therefore, perceived value is an important marketing concept that deals solely with the customer perception of a product. Perceived value is a consolidated measure because it takes into account subjective perception with limits placed on it by price and other subjective costs. A great deal of study on perceived value dimensions has been developed in order to measure the buyers’ perception towards products and services. This paper aims to examine the pre-purchase behavior by measuring effect on one of perceived value dimensions that covers emotional value, social value, functional value and perceived price on customer attitude and purchase intention. The research used the quantitative analysis research with the object of Nike sport shoes product in Pontianak and used the sample of 100 respondents in Pontianak by using the survey questionnaire as a guide. Data was analyzed with path analysis. The result shows that all the dimensions of perceived value have the positive and significant influence on customer attitude and purchase intention where emotional and functional value have the largest contribution, followed by social value and perceived price as the lowest contributors. Variable of customer attitude have a positive and significance towards purchase intention with a high contribution of more than 50%.   Keywords:   Emotional Value, Social Value, Functional Value, Perceived Price, Customer Attitude, Purchase intention